The impact of noise on human health and the environment - Zadro, Lea; Kalambura, Sanja (Crisis Management Days, 2024)
This research paper deals with the problem of noise and analyses the relevant legal framework in the Republic of Croatia that regulates noise levels for the protection of health and the environment. Noise is recognized as a significant factor that can affect people’s quality of life. Therefore, it is important to understand its impact and implement appropriate measures to address this challenge. The analysis of the legal framework shows that there are legal instruments, such as the Noise Abatement Act, which prescribe measures to prevent the negative effects of noise on human health and the environment. The measurement of internal and external noise was carried out with the Sauter SU 130, version 2.0. 04/2020, DE, which provides information about the actual noise levels in the analysed facility, a healthcare facility in Zagreb. Internal noise is often caused by staff and patient conversations and equipment, while external noise can be caused by traffic or other external sources. These findings provide a basis for understanding the challenges faced by workers and patients. The subjective experience of noise exposure is further analyzed in a survey of healthcare facility staff. The frequency of noise exposure, perceptions of the impact on concentration and productivity, and emotional reactions such as stress and sleep problems were analyzed to better understand the physical and psychological impact of noise on employees. The research also analyses employee awareness of noise-related regulations and policies and suggests measures to improve the situation. Indoor noise measurements with closed windows showed a deviation of 13.33% from the prescribed average noise level in a total of 60 measurements, while the deviation with open windows was 73.33%. The overall mean value of the noise measurement with closed windows is 42.9 dB(A), with the lowest mean value being 33.0 dB(A) and the lowest peak value 39.6 dB(A), while the highest mean value is 56.7 dB(A) and the highest peak value 73.6 dB(A). The average noise measurement with the windows open is 52.4 dB(A) overall, with the lowest mean value at 44.3 dB(A) and the lowest peak value at 48.1 dB(A), while the highest mean value is 59.0 dB(A) and the highest peak value is 71.2 dB(A). It is obvious that the noise levels are not satisfactory, and this experiment and analysis confirm a significant difference in noise levels between open and closed windows. The outdoor noise measurements showed a deviation of 38.33% from the average noise level with high peaks in a total of 60 measurements, which poses a potential risk to the health and quality of life of the exposed population. The lowest mean value is 57.2 dB(A), the lowest peak value is 64.7 dB(A), the highest mean value is 71.7 dB(A) and the highest peak value is 95.0 dB(A). High noise levels can also cause stress and disturbance to animals and disrupt their natural habitat and the balance of the ecosystem. In this part of the study, it was found that some of the noise levels do not meet the prescribed standard. A survey with 14 questions and 46 respondents revealed that noise is perceived as a potential disturbance and threat to one’s health and ability to work. Disappointing results were also obtained regarding knowledge of noise protection regulations and guidelines: 82.6 % of respondents had insufficient or no knowledge of noise legislation and recommendations. This part of the study confirmed the negative effects of noise on personal mood and functioning in the workplace as well as the insufficient knowledge of the legal framework. In conclusion, the study emphasises the importance of a systematic approach to noise management to protect human health and recommends further steps to implement effective noise reduction measures.